Chemical Exposure Due to Anthropogenic Ocean Acidification Increases Risks for Estuarine Calcifiers in the Salish Sea: Biogeochemical Model Scenarios - Nina Bednaršek; Greg Pelletier; Anise Ahmed; Richard A. Feely (Frontiers in Marine Science, 2020)
Ocean acidification (OA) is projected to have profound impacts on marine ecosystems and resources, especially in estuarine habitats. Here, we describe biological risks under current levels of exposure to anthropogenic OA in the Salish Sea, an estuarine system that already experiences inherently low pH and aragonite saturation state (Ωar) conditions. We used the Pacific Northwest National Laboratory and Washington State Department of Ecology Salish Sea biogeochemical model (SSM) informed by a selection of OA-related biological thresholds of ecologically and economically important calcifiers, pteropods, and Dungeness crabs. The SSM was implemented to assess current exposure and associated risk due to reduced Ωar and pH conditions with respect to the magnitude, duration, and severity of exposure below the biological thresholds in the Salish Sea in comparison to the pre-industrial era. We further investigated the individual effects of atmospheric CO2 uptake and nutrient-driven eutrophication on changes in chemical exposure since pre-industrial times. Our model predicts average decreases in Ωar and pH since pre-industrial times of about 0.11 and 0.06, respectively, in the top 100 m of the water column of the Salish Sea. These decreases predispose pelagic calcifiers to increased duration, intensity, and severity of exposure. For pteropods, present-day exposure is below the thresholds related to sublethal effects across the entire Salish Sea basin, while mortality threshold exposure occurs on a spatially limited basis. The greatest risk for larval Dungeness crabs is associated with spatially limited exposures to low calcite saturation state in the South Sound in the springtime, triggering an increase in internal dissolution. The main anthropogenic driver behind the predicted impacts is atmospheric CO2 uptake, while nutrient-driven eutrophication plays only a marginal role over spatially and temporally limited scales. Reduction of CO2 emissions can help sustain biological species vital for ecosystem functions and society.